ENERGY METABOLISM OF PACKED WHITE CELLS AFTER CRYOPRESERVATION AND REHABILITATION IN A MEDIUM CONTAINING A CORD BLOOD LOW-MOLECULAR FRACTION - A. K.; Yu. S.; А. А.; I. V. (Biotechnologia Acta, 2015)
To study the bioenergy indicators of leykokontsentrate cells after cryopreservation and the possibility of their recovery after incubation in a medium with a low-molecular fraction from cow cord blood were the aim of research. Leykokontsentrate was obtained from donor blood by sedimentation; cryopreservation was carried in the slow freezing regimen with 5% dimethylacetamide; amount of ATP, ADP and AMP was determined by chemiluminescence; glycogen — by cytochemical method. Evidence of energy disbalance of leukoconcentrate cells after cryopreservation was obtained. It was shown that the cord blood low-molecular fraction (0.15 mg/ml) activated glycogenolysis and increased contents of ATP, ADP and AMP in leukoconcentrate cells after cryopreservation. It was also shown that the cord blood low-molecular fraction contained energy substrates and metabolites, hormones and macro- and micronutrients. Use of the low-molecular fraction (below 5 kDa) from cord blood as a component of rehabilitating medium for frozen-thawed leukoconcentrate cells contributed to improvement of their energy status, which was manifested as augmentation in the total adenylic pool and glycogenolysis activation.